Cardiac regeneration: 20 years of development and update in zebrafish and mouse - Lekun Gui; Lijun Jin; Huangjun Liu (All Life)
Cardiovascular diseases are one of the leading causes of death globally. The primary pathological mechanism in myocardial infarction and heart failure is irreversible cardiomyocyte loss. The conventional knowledge is that mammals have a transient cardiac regenerative potential shortly after birth, but adult cardiomyocytes, as terminally differentiated cells, cannot regenerate. In contrast, some lower vertebrates, such as zebrafish, regenerate cardiac muscle throughout their lifetime. Zebrafish are extremely sensitive to cardiac injury and, within a short period, stimulate the proliferation of cardiomyocytes in numbers that fully regenerate to pre-injury levels; meanwhile, the initial scarring is gradually absorbed until there is little or no visible sign of fibrosis in the regenerating myocardium. The newborn mouse heart has the same remarkable regenerative potential before birth as one week after cardiac injury. The complex process of regeneration restores tissue structure through a series of cascade events, a coordinated process of cell proliferation, differentiation and dedifferentiation, and rearrangement of tissue morphogenesis. Understanding the ontogeny and development of cardiac regeneration and the molecular mechanisms of cardiac regeneration in zebrafish and mice is the cornerstone of regenerative biology and provides clues to investigate the cardiac repair process in adult mammals, resulting in extensive scarring rather than cardiomyocyte regeneration.